2022
DOI: 10.1038/s41597-022-01795-4
|View full text |Cite
|
Sign up to set email alerts
|

On-field optical imaging data for the pre-identification and estimation of leaf deformities

Abstract: Visually nonidentifiable pathological symptoms at an early stage are a major limitation in agricultural plantations. Thickness reduction in palisade parenchyma (PP) and spongy parenchyma (SP) layers is one of the most common symptoms that occur at the early stage of leaf diseases, particularly in apple and persimmon. To visualize variations in PP and SP thickness, we used optical coherence tomography (OCT)-based imaging and analyzed the acquired datasets to determine the threshold parameters for pre-identifyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The high level of scattering in the epidermal layers suggested that the leaves were infected with Cymbidium Mosaic Virus (CymMV), as confirmed by the enzyme-linked immunosorbent assay (ELISA) test, which is the current gold standard test for detecting virus infection in orchid plants. In our previously published article, a threshold for the pre-identification of palisade parenchyma (PP) and spongy parenchyma (SP) layer anomalies in persimmon and apple-leaf specimens was defined using the depth profile approach, based on OCT cross-sections [ 64 ]. A set of OCT cross-sectional images of apple and persimmon leaves were employed to quantitatively evaluate the inner structure of the leaf specimens, where it was observed that the thickness between the PP and SP layers gradually decreased in apparently healthy leaves and merged in infected apple leaves.…”
Section: Chaptersmentioning
confidence: 99%
See 3 more Smart Citations
“…The high level of scattering in the epidermal layers suggested that the leaves were infected with Cymbidium Mosaic Virus (CymMV), as confirmed by the enzyme-linked immunosorbent assay (ELISA) test, which is the current gold standard test for detecting virus infection in orchid plants. In our previously published article, a threshold for the pre-identification of palisade parenchyma (PP) and spongy parenchyma (SP) layer anomalies in persimmon and apple-leaf specimens was defined using the depth profile approach, based on OCT cross-sections [ 64 ]. A set of OCT cross-sectional images of apple and persimmon leaves were employed to quantitatively evaluate the inner structure of the leaf specimens, where it was observed that the thickness between the PP and SP layers gradually decreased in apparently healthy leaves and merged in infected apple leaves.…”
Section: Chaptersmentioning
confidence: 99%
“…( i ( a – c )) OCT cross-sectional images of persimmon leaves. ( i ( d – f )) OCT cross-sectional images of apple leaves (figure source [ 64 ]). ( ii ) Depth profiles of healthy, apparently healthy, and infected apple leaves; ( ii ( a , b )), ( ii ( c , d )), and ( ii ( e , f )) show the depth profiles of healthy, apparently healthy, and infected apple leaves, respectively.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…OCT has also been used in biomedical and clinical investigations in dermatology [25], ophthalmology [26], gastroenterology [27], dentistry [28], otorhinolaryngology [29,30], otology [31], and oncology [32]. Furthermore, OCT is diversely used in multidisciplinary fields, such as industrial evaluation [33], agriculture [34,35], and entomology [36,37]. Non-invasive OCT imaging technology facilitates the investigation of the morphology of sweat ducts [38,39], the qualitative morphological analysis of normal skin [25], and the visualizing of the anatomical structures in biological tissues [40].…”
Section: Introductionmentioning
confidence: 99%